2010
DOI: 10.1111/j.1567-1364.2009.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple effects of amprenavir againstCandida albicans

Abstract: Secreted aspartyl peptidases (Saps) are virulence attributes produced by Candida albicans that participate in multiple aspects of the fungal biology and pathogenesis. In the present paper, we have shown that amprenavir, a peptidase inhibitor used in HIV chemotherapy, inhibited Sap2 and growth of C. albicans and also promoted ultrastructural alterations. Esterase activity, sterol content, biofilm formation and the expression of surface mannose- and sialic acid-rich glycoconjugates were also reduced by amprenavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 20 publications
3
72
0
2
Order By: Relevance
“…Braga-Silva et al (2010) showed that amprenavir reduced the expression of surface mannose-and sialic acid-rich glycoconjugates also inhibited esterase activity, sterol content and biofilm formation in C. albicans. The adhesion of Candida sp.…”
Section: Antiretroviral Drugs and Fungal Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Braga-Silva et al (2010) showed that amprenavir reduced the expression of surface mannose-and sialic acid-rich glycoconjugates also inhibited esterase activity, sterol content and biofilm formation in C. albicans. The adhesion of Candida sp.…”
Section: Antiretroviral Drugs and Fungal Agentsmentioning
confidence: 99%
“…The same protease inhibitors can act directly on SAPs 1, 2 and 3, but not on SAPs 4, 5 and 6, inhibiting several relevant biological processes of C. albicans, such as growth and adhesion to mammalian cells (Bektic et al, 2001;Blanco et al, 2003;Borg-von Zepelin et al, 1999;Braga-Silva et al, 2010;Cassone et al, 1999;Falkensammer, Pilz, Bektic, 2007;Gruber et al, 1999;Korting et al, 1999;Monod et al, 1999). Braga-Silva et al (2010) showed that amprenavir reduced the expression of surface mannose-and sialic acid-rich glycoconjugates also inhibited esterase activity, sterol content and biofilm formation in C. albicans.…”
Section: Antiretroviral Drugs and Fungal Agentsmentioning
confidence: 99%
“…albumin and hemoglobin) as a unique nitrogenous source, but not when Candida cells are cultured in a medium containing an unlimited nitrogenous source [104][105][106][107][108] ; (2) Some intracellular aspartic proteases produced by microorganisms also control the cleavage of important own proteins in order to promote protein activation and/or perfect functioning of a biosynthetic route; their inhibition can arrest signaling events and/or metabolic pathways, as a result inhibiting some crucial biological processes for microbial cells such as morphogenesis or expression of surface molecules responsible for adhesion or fungal protection. For example, some of these aspartic protease inhibitors alter the lipid biosynthesis, including ergosterol, resulting in altered membrane permeability [68,72,83] . These inhibitory actions will depend on the ability of the aspartic protease inhibitors to (a) enter in the microbial cells and (b) accumulate inside them; and (3) Some surface aspartic proteases participate in the assembly and organization of the microbial surface.…”
Section: F Pedrosoimentioning
confidence: 99%
“…Several surface and/or secreted molecules have had their expression/production significantly diminished including (1) mannose-and sialic acidrich surface glycoconjugates, which are directly involved in adhesive properties and biofilm formation; (2) sterol content, which controls the membrane fluidity; (3) secretion of lipases (e.g. esterases and phospholipases), which are related to the host membrane disruption; and (4) catalase activity, which reduces the ability of yeasts to escape from oxidative stress generated by hydrogen peroxide, for example, released by host phagocytes [72] (unpublished data). However, it is also important to note that the inhibitory effects of HIV protease inhibitors both in in vitro and in vivo experimental models were observed at concentrations (μmol/L range) much higher than those needed for HIV protease inhibition (nmol/L range).…”
Section: Tripeptidyl Peptidases Dipeptidyl Peptidasesmentioning
confidence: 99%
See 1 more Smart Citation